Miscommunication and Conflict Resolution in Monogamous Relationships - Khaerudin Imawan; Azfa Kautsar Hammami (CV. Media Digital Publikasi Indonesia, 2026)
Miscommunication is cognitive-affective dissonance that happens during message transaction with potential disturbances of significant meaning transfer and relationship imbalance in relation to romantic associations. For monogamously related individuals, miscommunication is often expressed through relationship conflict which necessitates an efficient conflict resolution strategy to preserve relationship stability as well as relationship quality for a couple. The aim of this research is to examine and clarify (phénomènonlogically) the phenomenon of miscommunication dynamics and importantly, the mediating influence of assertive communication based on conflict resolution technique according to Robert E. Alberti and Michael L. Emmons’ Assertiveness Theory theory outline. Essentially, this research is meant to assess kinds of miscommunication experiences of relations, influence of miscommunication on relationship quality, as well as mediating influence of assertive communication as a link for understanding notions of differences of perspectives according to prior theoretical outline for effective conflict resolution for relations of all kinds. Research method qualifies as phenomenological with application of key participants’ analysis through intensive interviews with respondents. Expected findings for current research are supposed to give significant contribution to truth through technique application of promoting healthier relations with clearer and more meaningful communication through principles of assertive communication according to research outline aims objectives.